Capsular Polysaccharide is a Main Component of Mycoplasma ovipneumoniae in the Pathogen-Induced Toll-Like Receptor-Mediated Inflammatory Responses in Sheep Airway Epithelial Cells - Zhongjia Jiang; Fuyang Song; Yanan Li; Di Xue; Guangcun Deng; Min Li; Xiaoming Liu; Yujiong Wang (Hindawi Limited, 2017)
Mycoplasma ovipneumoniae (M. ovipneumoniae) is characterized as an etiological agent of primary atypical pneumonia that specifically infects sheep and goat. In an attempt to better understand the pathogen-host interaction between the invading M. ovipneumoniae and airway epithelial cells, we investigated the host inflammatory responses against capsular polysaccharide (designated as CPS) of M. ovipneumoniae using sheep bronchial epithelial cells cultured in an air-liquid interface (ALI) model. Results showed that CPS derived from M. ovipneumoniae could activate toll-like receptor- (TLR-) mediated inflammatory responses, along with an elevated expression of nuclear factor kappa B (NF-κB), activator protein-1 (AP-1), and interferon regulatory factor 3 (IRF3) as well as various inflammatory-associated mediators, representatively including proinflammatory cytokines, such as IL1β, TNFα, and IL8, and anti-inflammatory cytokines such as IL10 and TGFβ of TLR signaling cascade. Mechanistically, the CPS-induced inflammation was TLR initiated and was mediated by activations of both MyD88-dependent and MyD88-independent signaling pathways. Of importance, a blockage of CPS with specific antibody led a significant reduction of M. ovipneumoniae-induced inflammatory responses in sheep bronchial epithelial cells. These results suggested that CPS is a key virulent component of M. ovipneumoniae, which may play a crucial role in the inflammatory response induced by M. ovipneumoniae infections.